HR-LC-ESI-Orbitrap-MS-Based Metabolic Profiling Coupled with Chemometrics for the Discrimination of Different Echinops spinosus Organs and Evaluation of Their Antioxidant Activity - Amel Bouzabata; Paola Montoro; Katarzyna Angelika Gil; Sonia Piacente; Fadia S. Youssef; Nawal M. Al Musayeib; Geoffrey A. Cordell; Mohamed L. Ashour; Carlo Ignazio Giovanni Tuberoso (MDPI AG, 2022)
This study aimed to assess and correlate the phenolic content and the antioxidant activity of the methanol extracts of the stems, roots, flowers, and leaves of Echinops spinosus L. from north-eastern Algeria. Qualitative analysis was performed by high-resolution mass spectrometry (HR) LC-ESI-Orbitrap-MS and (HR) LC-ESI-Orbitrap-MS/MS). Forty-five compounds were identified in the methanol extracts; some are described for the first time in E. spinosus. Targeted phenolic compounds were quantified by HPLC-DAD and it was shown that caffeoyl quinic derivatives were the most abundant compounds. Chemometric analysis was performed using principal component analysis (PCA) and hierarchical cluster analysis (HCA) based on the qualitative and quantitative LC data. The score plot discriminates different Echinopsis spinosus organs into three distinct clusters, with the stems and flowers allocated in the same cluster, reflecting their resemblance in their secondary metabolites. The antioxidant activities of the methanol extracts were assessed using cupric reducing antioxidant capacity (CUPRAC), ferric reducing antioxidant assay (FRAP), diphenyl picryl hydrazyl radical-scavenging capacity assay (DPPH●), and 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS●+). The root extract exhibited the highest antioxidant activity, evidenced by 3.26 and 1.61 mmol Fe2+/g dried residue for CUPRAC and FRAP, respectively, and great free radical-scavenging activities estimated by 0.53 and 0.82 mmol TEAC/g dried residue for DPPH● and ABTS●+, respectively. The methanol extract of the roots demonstrated a significant level of total phenolics (TP: 125.16 mg GAE/g dried residue) and flavonoids (TFI: 25.40 QE/g dried residue TFII: 140 CE/g dried residue). Molecular docking revealed that tricaffeoyl-altraric acid and dicaffeoyl-altraric acid exhibited the best fit within the active sites of NADPH oxidase (NO) and myeloperoxidase (MP). From ADME/TOPAKT analyses, it can be concluded that tricaffeoyl-altraric acid and dicaffeoyl-altraric acid also revealed reasonable pharmacokinetic and pharmacodynamic characteristics with a significant safety profile.